Multidisciplinary Assessment of Citizenship Approach in Modern Law and Problem of “Denaturalisation” on the Basis of Law and Communication - Dolunay, Ayhan; Keçeci, Gökçe (Journal of History Culture and Art Research, 2017)
Through the provision of general definition for the concepts of “modernisation” with many dimensions and “law”1 as there is no main consensus on the doctrine, our study discussed the concept of “modern law” reached through the related impacts” and addressed the issue of “denaturalisation”, which is defined as “against the modern law system” in the field of “cizitezenship law” as one of the modern law domains covering various concepts within, and is not under the scope of European Convention on Nationality and Turkish Law, however is covered under the applicable citizenship law of the Turkish Republic of Northern Cyprus and under the new law on citizenship aiming the revision of existing law and elaborated that the related issue is not only constitute a question of law but also with another significant aspect harms the communication and relationship between state-individual and state and other states/international organizations. Consequently, our study delivered concrete proposals to eliminate/prevent the divergences caused by the relevant organisation regarding the legal, communication and other domains of social sciences.